Employment Protection and Gross Job Flows: A Differences-in-Differences Approach - Alejandro Micco; Carmen Pagés-Serra (Inter-American Development Bank, Research Department, 2004)
This paper examines the effect of employment protection regulation on gross job flows in a sample of developed and developing countries. By implementing a differences-in-differences test we lessen the potentially severe endogeneity and omitted variable problems associated with cross-country regressions. This test is based on the hypothesis that job security regulations are more binding in some sectors of economic activity than in others, depending on sector-specific characteristics such as the variance of demand or technological shocks. Unlike most of the existing literature, our analysis indicates that more stringent job security regulations slow down gross job flows, and this tendency is more pronounced in sectors that require higher labor flexibility. These effects occur within the sample of developed and developing countries and are very large in magnitude. Moreover, these effects are robust to changes in regulatory measures, measurement of sector flexibility requirements, control variables and samples.
Keywords: 330; Arbeitnehmerschutz; Arbeitsmobilität; Vergleich; Welt